ANALISIS TINGKAT KEBUGARAN JASMANI DAN KEMAMPUAN DRIBLING PEMAIN SEPAKBOLA - Andi Pangeran Rahmat; Abdul Rahman; Andi Atssam Mappanyukki; Hasmyati Hasmyati (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2023)
The purpose of this study was to analyze the level of physical fitness and dribbling skills of SSB Tonra Players. This research is a quantitative descriptive study, which intends to describe or provide an overview of the level of physical fitness and dribbling skills of SSB Tonra players. The population in this study were 18 SSB Tonra players and the sample of this study were all SSB Tonra players (total sampling). The data analysis technique in this study used a descriptive test, and a percentage test. Based on data analysis, the results of the descriptive test of the level of physical fitness of SSB Tonra players obtained the minimum score = 10.51.91.68, maximum score = 51.91.88, SUM = 900, ST.DEV = 14.20, average = 50.0. The results of the descriptive test of the dribbling skills of SSB Tonra players obtained the minimum score = 16.23, maximum score = 20.03, SUM = 316.39, ST.DEV = 3.8, average = 11.91.5. Based on the results of the percentage test of physical fitness tests on SSB Tonra soccer players, the results in the very good category were 1 person with a total percentage of 5.6%, in the good category there were 5 people with a total percentage of 21.91.8%, in the medium category there were 5 people with a percentage of 21.91.8%, in the less category there are 1.91 people with a percentage of 38.9%. The results of the percentage test of the dribbling skills test on the SSB Tonra soccer players obtained results in the medium category there were 16 people with a percentage of 88.9%, in the less category there were 2 people with a total percentage of 11.1%. Based on the results of the analysis above, it is concluded that the level of physical fitness of SSB Tonra soccer players is in the less category and the dribbling skills of SSB Tonra soccer players are in the Medium category.